Navigating Uncharted Waters: Women Empowerment and Public Policy in the Context of the Arab Gulf States - Rabia Naguib (17884538) (2023)
This Open Access book offers a comprehensive examination of the various aspects of women’s empowerment and public policy in the Gulf Cooperation Council (GCC) countries, with a focus on Qatar. The GCC countries have made women’s empowerment a national priority and implemented policies in line with SDG5, which promotes gender equality. The book features qualitative research based on the experiences and perspectives of women, giving insight into how women’s empowerment is being envisioned and realized in the GCC context. The adopted context-driven approach considers local values and the Islamic worldview and highlights the ideological and epistemological challenges posed by the differences between Western and Majority-Muslim referential systems. This book provides a deeper and nuanced understanding of the complexities of promoting women’s empowerment in the GCC region and is a valuable resource for scholars and policymakers working on gender and empowerment, particularly in the Gulf and Arab world. Other Information Published in: Women's Empowerment and Public Policy in the Arab Gulf States : Exploring Challenges and Opportunities License: http://creativecommons.org/licenses/by/4.0/ See chapter on publisher's website: http://dx.doi.org/10.1007/978-981-99-6006-4_1